Synthesis of C/MoS2-CoMo2S4 for application in Li-O2 batteries. (20th March 2022) - Liu, Wenhong; Li, Yuanmei; Yuan, Huaibo; Wu, Xiaojing; Zhang, Dawei
Highlights: C/MoS2 CoMo2 S4 was prepared by calcining the hybrid of C/MoS2 and ZIF-67 at 800 °C. C/MoS2 CoMo2 S4 –800 is good cathode catalyst of Li-O2 batteries. The catalytic activity of C/MoS2 CoMo2 S4 –800 can be improved by acid pickling. The battery shows high discharge specific capacity and excellent cycle stability. Abstract: High efficiency electrocatalyst is the key factor to achieve high charge-discharge specific capacity and long cycle life of Li-O2 batteries (LOBs). In this work, the C/MoS2 CoMo2 S4 was successfully prepared by calcining the hybrid of ZIF-67 and C/MoS2 at 800 °C. The composite materials have three advantages for oxygen reduction and evolution reaction (ORR/OER) of LOBs, including highly efficient catalysis of CoMo2 S4, abundant porous network and a surface conducive to Li2 O2 precipitation. The LOBs with acid-pickled C/MoS2 CoMo2 S4 –800 showed a high discharge specific capacity (17, 551 mAh g −1 ) and an excellent cycle stability of 336 cycles at a current density of 500 mA g −1 and capacity limit of 1000 mAh g −1 . Interestingly, the catalytic activity of C/MoS2 CoMo2 S4 can be improved by acid pickling or the increasement of calcination temperature from 700 to 800 °C. Graphical abstract: Image, graphical abstract C/MoS2 was prepared by hydrothermal method. The C/MoS2 was dispersed in methanol solution containing 2-methylimidazole and Co 2+ . The mixture was stirred, extracted and washed to obtain ZIF-67-C/MoS2 which was calcined at 800 °C to obtain C/MoS2 CoMo2 S4 . The prepared materials were used for the cathode catalysts of LOBs, the battery showed a high discharge specific capacity (17, 551 mAh g −1 ) and an excellent cycle stability of 336 cycles.